Strategies of Sport Management for the Excellent Competition of Nongyama Municipal School (Municipal Sports School, Roi Et) - Panthu, Somboon (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2021)
The objectives of this research were to study strategies of sport management for excellent competitions of Nongyama Municipal School (Municipal Sports School, Roi Et) and to evaluate the appropriate of strategies of sport management for excellent competitions. The target population consisted of School executives, sport-related personals, managers, instructors, and athletes - totally 122 people. The instruments were the interview form and questionnaires. Statistics used in data analysis were mean and standard deviation. The results of the research were as follows: 1. The current sport management strategies with regards to the policies, directives, and visions of the School were placing a strong emphasis on planned operations, and budget appropriations in order to achieve maximum benefits. The current strategies established and developed the existing sport management team-the unit responsible for supporting, improving morale of both instructors and athletes with an additional task of carrying out follow-up evaluations of executed operations. 2. From the analysis, it was found that all the aspects were rated at a moderate level. The problem of sport management was at a moderate level. 2. The members generated six strategies as follows: strategy 1 searching for highly talented athletes to join the School team; strategy 2 developing and improving athletes' skills for competitions; strategy 3 improving both athletes' and instructors' morale; strategy 4 providing standard sport fields and practice equipments; strategy 5 creating strong sport management team; strategy 6 conducting sport evaluation and advertising for the School. 3. The evaluation concluded that the six sport management were appropriate and were within the acceptable criteria.